FROM EXPERIENCE TO ALGORITHM: THE EFFECTIVENESS OF ROBOTIC KNEE ARTHROPLASTY IN LIGHT OF THE LATEST RESEARCH - Adam Solarz; Szymon Szabelski; Joanna Kryślak; Maciej Sokołowski; Karolina Oskroba (International Journal of Innovative Technologies in Social Science, 2025)
Total knee arthroplasty (TKA) is one of the most commonly performed and most effective procedures for the treatment of knee osteoarthritis (gonarthrosis). Despite its great clinical success, the procedure remains a technical challenge for the entire surgical team, and the selection of appropriate implants as well as achieving proper soft tissue balance are key factors influencing long-term treatment outcomes. In recent years, robotic assistance has been introduced in this procedure, significantly improving functional outcomes and reducing complication rates. This article discusses the latest research on robotic-assisted total knee arthroplasty. Objective: A review of selected articles, literature, and the latest reports on the using robotic surgery in total knee arthroplasty. Materials and Methods: A literature review of scientific articles available on PubMed and Google Scholar.